North–South Cooperation in Higher Education: Revisiting International Aid Flows - Pedró, Francesc (International Higher Education, 2022)
This article provides an exploratory overview of international aid devoted to higher education, including its relative importance compared to other types of aid, its main characteristics and geographical distribution patterns, as well as a list of main donors, recipients, and channels. It sets a common and global baseline that may contribute to a global, evidence-based reflection and debate around this topic including all stakeholders, and to changes in the current paradigm.